Technical Indicators of Cardio-Pulmonary Resuscitation (Cpr) with Traveling Time 20, 40 and 60 Km/H - Yogo Apriyanto; Nursalam Nursalam; Arie Sunarno (Universitas Airlangga, 2010)
Introduction: Ambulances had special rule of velocity. Ambulances could accelerate over 80 km/h and could break through traffic light. During transport the patient might be got cardiac arrest. Almost all of the pre hospital nurses had reported that doing CPR during transport was difficult. The objective of this study was to analyze the effect of traveling time 20 km/h, 40 km/h and 60 km/h on technical indicators of CPR.Methods: Design used in this study was pre-experiment. The population were nurses in ambulances 118 of Dr. Soetomo hospital Surabaya. A total of 14 respondents were taken as samples by purposive sampling. The independent variable was effectiveness of traveling time, while the dependent variable were technical indicators of CPR: Tidal Volume (TV), landmark hand position, deep of chest compression and chest compression rhythm in manekin. Data were measured by observation sheet and then analyzed using Chi-square test with level of significance α ≤ 0.05.Result: The result showed that travelling time 20 km/h and 40 km/h had a significant effect on technical indicators of CPR, but not at 60 km/h.Conclusion: It could be concluded, the faster the travelling time, the more difficult to perform CPR. Further study should involve the travelling time and the accuracy of CPR technical indicators to treat and safe the patients, either in traumatic or non traumatic case.